'We All Speak Football': An Investigation of the Benefits of A Consumer-oriented, Globally Integrated Marketing Communications Campaign in The Context of The Sponsorship of A Major International Sporting Event: A Case Study on the Coca-Cola Company and the 2006 FIFA World Cup - Capewell, Luke (2006)
(Globally) Integrated Marketing Communications (GIMC) has received considerable attention within academic literature over the past twenty years and has provoked important debates. Despite this, many authors have merely concentrated on the potential benefits that can be acquired. Although some have highlighted the problems with implementation and the need for an outside-in approach, this case study emphasizes the importance of public perception, market alterations, changes in demand and the importance of obtaining and maintaining a creditable link between the product and the event being sponsored.